Palladium-Catalyzed [4+2] Annulation of Aryl and Alkenyl Carboxamides with 1,3-Dienes via C–H Functionalization: Synthesis of 3,4-Dihydroisoquinolones and 5,6-Dihydropyridinones - Sun, Manman; Li, Jinshan; Chen, Weida; Wu, Haijian; Yang, Jianguo; Wang, Zhiming (Synthesis, 2020)
Palladium-catalyzed [4+2] annulation of aryl and alkenyl carboxamides with 1,3-dienes via C–H functionalization is developed using air as the terminal oxidant. The method demonstrates good functional group tolerance and high stereoselectivity, affording a series of 3,4-dihydroisoquinolones and 5,6-dihydropyridinones in yields of up to 99%.
Keywords: palladium; [4+2] annulation; carboxamides; dienes; C–H functionalization; 3,4-dihydroisoquinolones; 5,6-dihydropyridinones